Exposure of Microglia to Interleukin-4 Represses NF-κB-Dependent Transcription of Toll-Like Receptor-Induced Cytokines - Zuiderwijk-Sick, Ella A.; van der Putten, Céline; Timmerman, Raissa; Veth, Jennifer; Pasini, Erica M.; van Straalen, Linda; van der Valk, Paul; Amor, Sandra; Bajramovic, Jeffrey J. (Frontiers in Immunology, 2021)
Interleukin (IL)-4 is a cytokine that affects both adaptive and innate immune responses. In the central nervous system, microglia express IL-4 receptors and it has been described that IL-4-exposed microglia acquire anti-inflammatory properties. We here demonstrate that IL-4 exposure induces changes in the cell surface protein expression profile of primary rhesus macaque microglia and enhances their potential to induce proliferation of T cells with a regulatory signature. Moreover, we show that Toll like receptor (TLR)-induced cytokine production is broadly impaired in IL-4-exposed microglia at the transcriptional level. IL-4 type 2 receptor-mediated signaling is shown to be crucial for the inhibition of microglial innate immune responses. TLR-induced nuclear translocalization of NF-κB appeared intact, and we found no evidence for epigenetic modulation of target genes. By contrast, nuclear extracts from IL-4-exposed microglia contained significantly less NF-κB capable of binding to its DNA consensus site. Further identification of the molecular mechanisms that underlie the inhibition of TLR-induced responses in IL-4-exposed microglia may aid the design of strategies that aim to modulate innate immune responses in the brain, for example in gliomas.